Analysis of the technology to manufacture a high-temperature microstrip superconductive device for the electromagnetic protection of receivers - Fyk, Oleksandr; Kucher, Dmytro; Kucher, Larisa; Gonchar, Roman; Antonetsʹ, Volodymyr; Fyk, Mykhailo; Besedin, Yuri (Eastern-European Journal of Enterprise Technologies, 2018)
Technological features of the process of manufacturing a high-speed high-temperature superconducting microstrip protective device which can reduce in a picosecond period (the time of switching or operation speed) the incoming power from the antenna-feeder path and the power passing through it to a level safe for sensitive semiconductor elements of the receiver (preventing current destruction of p-n junction). The study enables determination of the features and conditions for the use of modern technological methods for creating a superconducting microstrip protective device taking into account influence of the substrate material, superconductor and contacts and the method of their connection on the switching properties of superconducting films of the proposed protective device. The switching properties of superconducting films include speed of phase transition of a film from a superconducting to a nonconducting state. To determine degree of material influence on switching properties, it was proposed to use the following: lattice parameter, thermal expansion coefficient of materials, degree of interaction of molecular structures of the contacting surfaces, probability of local defects on the surface (nonconducting zones). The study outlines basic conditions (methods of film deposition, applying a certain superconducting film (YBCO) on the chosen substrate) which should be met in order to create an operable protective device. The study results make it possible to assess the degree of influence of contact materials and the method of deposition (of both film on the substrate and contacts on the film) on microstructure and switching properties of the superconducting protective device. Such results can be used in synthesis of high-temperature superconducting devices for protecting receiver elements from current destruction of their p–n junctions